Reviewing Critical Research Methodologies for Teacher Education in Applied Linguistics - Magalhães, Maria Cecilia Camargo; Fidalgo, Sueli Salles (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The ﬁeld of Applied Linguistics has undergone several changes in the last years, and, in various aspects, it can be considered today as movable praxis (Pennycook, 2001:173). This text reviews Critical Research Methodologies, by ﬁrstly looking at the history of the ﬁeld, and analyzing how it has changed over the years, comparing such methodologies as Action Research (AR); Participative Research (PR) and Critical Collaborative Research (PCCol) considering that these, to a greater or lesser degree, intervene in the context where they organize the research carried out. We then deepen our discussion of PCCol – theory-methodology used by our research groups: LACE, ILCAE and GEICS.